Evaluating Effects of Electric Vehicle Chargers on Residential Power Infrastructure - Pathomthat Chiradeja; Orawan Chuadmee; Santipont Ananwattanaporn; Chayanut Sottiyaphai; Atthapol Ngaopitakkul (Applied Sciences, 2025)
This study investigated the impact of electric vehicle (EV) chargers on residential electrical systems through a real-world case study in a condominium located in Bangkok, Thailand. A two-week field measurement was conducted to analyze load profiles, current and voltage behavior, phase symmetry, and harmonic distortion during EV charger operation. The results show that single-phase charging dominated usage patterns, leading to phase imbalance and significant neutral current flow. Voltage unbalance was quantified using the maximum deviation method, with an average value of 0.535 percent and a peak of 2.18 percent observed during charging activity. A harmonic distortion analysis revealed a substantial increase in current total harmonic distortion (THD) during active charging, with values rising to between 15 and 20 percent. These findings highlight nonlinear loading effects that may reduce power quality and pose risks to electrical equipment and system stability. In retrofitted electrical infrastructures, these effects are often exacerbated by design limitations and the absence of coordinated load management. This study’s findings offer practical insights for engineers, facility managers, and policymakers in designing EV-ready residential systems that are both efficient and resilient.
Keywords: Electric Vehicles and Infrastructure; Advanced Battery Technologies Research; Electric and Hybrid Vehicle Technologies